Activity-Based Anorexia Reduces Body Weight without Inducing a Separate Food Intake Microstructure or Activity Phenotype in Female Rats—Mediation via an Activation of Distinct Brain Nuclei - Scharner, Sophie; Prinz, Philip; Goebel-Stengel, Miriam; Kobelt, Peter; Hofmann, Tobias; Rose, Matthias; Stengel, Andreas (Frontiers in Neuroscience, 2016)
Anorexia nervosa (AN) is accompanied by severe somatic and psychosocial complications. However, the underlying pathogenesis is poorly understood, treatment is challenging and often hampered by high relapse. Therefore, more basic research is needed to better understand the disease. Since hyperactivity often plays a role in AN, we characterized an animal model to mimic AN using restricted feeding and hyperactivity. Female Sprague-Dawley rats were divided into four groups: no activity/ad libitum feeding (ad libitum, AL, n=9), activity/ad libitum feeding (activity, AC, n=9), no activity/restricted feeding (RF, n=12) and activity/restricted feeding (activity-based anorexia, ABA, n=11). During the first week all rats were fed ad libitum, ABA and AC had access to a running wheel for 24h/d. From week two ABA and RF only had access to food from 9:00-10:30 am. Body weight was assessed daily, activity and food intake monitored electronically, brain activation assessed using Fos immunohistochemistry at the end of the experiment. While during the first week no body weight differences were observed (p>0.05), after food restriction RF rats showed a body weight decrease: -13% vs. day eight (p<0.001) and versus AC (-22%, p<0.001) and AL (-26%, p<0.001) that gained body weight (+10% and +13%, respectively; p<0.001). ABA showed an additional body weight loss (-9%) compared to RF (p<0.001) reaching a body weight loss of -22% during the 2-week restricted feeding period (p<0.001). Food intake was greatly reduced in RF (-38%) and ABA (-41%) compared to AL (p<0.001). Interestingly, no difference in 1.5-h food intake microstructure was observed between RF and ABA (p>0.05). Similarly, the daily physical activity was not different between AC and ABA (p>0.05). The investigation of Fos expression in the brain showed neuronal activation in several brain nuclei such as the supraoptic nucleus, arcuate nucleus, locus coeruleus and nucleus of the solitary tract of ABA compared to AL rats. In conclusion, ABA combining physical activity and restricted feeding likely represents a suited animal model for AN to study pathophysiological alterations and pharmacological treatment options. Nonetheless, cautious interpretation of the data is necessary since rats do not voluntarily reduce their body weight as observed in human AN.